Maternal Physiological Parameters in Relationship to Systemic Inflammatory Response Syndrome Criteria. Issue 3 (September 2015) - Bauer, M.E.; Bauer, S.T.; Rajala, B.; MacEachern, M.P.; Polly, L.S.; Childers, D.; Aronoff, D.M.
<x xml:space="preserve">Abstract</x> (Obstet Gynecol. 2014;124(3):535–541)